The Implementaion Strategical Of Human Resource System Towards The Globalization Challenges : Review International Articles - Ai Suminar; Edi Putra Telaumbanua (OIKONOMIA: Journal of Economics and Management Science, 2023)
This study is a form of review study related to the implementation of human resources. Especially, at this time which refers to the form of globalization. As is known, the form of globalization is a stage of development that is able to influence and trigger a process of change in human life so that it becomes one of the main parts of the foundation related to human information systems. The main purpose of this study is to determine the form of influence given from the determination of a human resource to the current technological challenges. The method used in this study is a form of literature study method by applying elements of qualitative methods from various journals. The results of the study show some of the major influences that occur due to globalization on human resources which refer to several results, namely; (1) Cultural changes applied to the human resources section, which causes these human resources to become more effective and even become a major assessment in the form of future changes; (2) the type of productivity used to improve the quality of community performance, especially in the field of greater manufacturing; (3) the advantages and disadvantages of aspects of globalization that allow people to understand more and keep up with the times. The role of these three influences is more about the consequences of globalization so that it is widely applied to industries such as business or other industries. However, the context of a globalization is more reflective of how or describe a link of technological reasoning in the study that is able to connect and connect all related objects from these parts.